Synoptic Operative Reporting: Documentation of Quality of Care Data for Rectal Cancer Surgery. Issue 3 (March 2020) - Robertson, Reagan L.; Vergis, Ashley
Operative reports can be used to evaluate quality of care indicators in surgical patients. This study evaluated documentation of preoperative and intraoperative quality of care indicators for rectal cancer surgery in synoptic reports and traditional dictated reports. Two surgeons independently reviewed 40 prospectively collected synoptic operative reports from rectal cancer cases and a case-matched historical cohort of 40 dictated reports. Rectal cancer–specific quality measures were scored in both report groups using two separate, previously validated checklists. Synoptic reports had significantly higher overall scores on both checklists 1 (mean adjusted score ± SD 76 ± 4 vs 41 ± 19, P < 0.01) and 2 (54 ± 3 vs 24 ± 11, P < 0.01; maximum score of 100 for both checklists). Synoptic reports scored significantly higher in reporting preoperative and intraoperative care indicators. Data were extracted quickly from synoptic reports (mean 3:46 vs 6:21, minutes:seconds to complete checklists, P < 0.05). Synoptic reports are associated with accurate documentation of quality of care data for rectal cancer surgery. Refining the synoptic templates used will further enhance the collection of quality indicators and reporting in complex oncologic procedures.